"Buck and Ball": Identification and interpretation of buckshot injuries to the pelvis from the War of 1812. (April 2016) - Lockau, Laura; Gilmour, Rebecca; Menard, Jean-Paul; Balakrishnan, Narayanaswamy; Dragomir, Ana-Maria; Mant, Madeleine; Watamaniuk, Lelia; Brickley, Megan
Abstract: During the War of 1812, the flintlock smoothbore musket represented a significant cause of injury and death. Putative musket ball and buckshot injuries were observed in the skeletal remains of individuals from the Smith's Knoll collection, comprised of soldiers killed during the battle of Stoney Creek (1813, Ontario, Canada). In order to confirm the identification of three impacts from buckshot ammunition in two innominates from this assemblage, faunal proxies were shot using a replica War of 1812 flintlock smoothbore musket and ammunition. Experimental research also aimed to evaluate whether the spacing of lesions could be related to impact characteristics such as projectile velocity as associated with range of fire. Significant differences in distance values for lesion spread were found between shots taken from distances of 9.14 and 18.29 m (10 and 25 yards), however, there was some overlap between the ranges for these distances. While the small distance between archaeological injuries suggests they are more likely to result from a shot taken at a closer range of fire, a shot from further away cannot be ruled out. The archaeological lesions display characteristics associated with musket injuries, and their sizes correspond specifically to the experimental injuries caused by buckshot ammunition. This represents the first identification of buckshot injuries in archaeological skeletal material. Highlights: Musket ball and putative buckshot injuries were identified in three innominates. Closely spaced lesions are more likely to correspond to a smaller range of fire. Experimental proxies confirmed the presence of buckshot lesions in two innominates. This is the first identification of buckshot injuries in archaeological human bone.